Science Fiction Literature in East Germany - Fritzsche, Sonja (DDR- Studien / East German Studies, 2018)
East German science fiction enabled its authors to create a subversive space in another time and place. One of the country's most popular genres, it outlined futures that often went beyond the party's official version. Many utopian stories provided a corrective vision, intended to preserve and improve upon East German communism. This study is an introduction to East German science fiction. The book begins with a chapter on German science fiction before 1949. It then spans the entire existence of the country (1949-1990) and outlines key topics essential to understanding the genre: popular literature, socialist realism, censorship, fandom, and international science fiction. An in-depth discussion addresses notions of high and low literature, elements of the fantastic and utopia as critical narrative strategies, ideology and realism in East German literature, gender, and the relation between literature and science. Through a close textual analysis of three science fiction novels, the author expands East German literary history to include science fiction as a valuable source for developing a multi-faceted understanding of the country's short history. Finally, an epilogue notes new titles and developments since the fall of the Berlin Wall.